Where have all the flower children gone? - Gurvis, Sandra (University Press of Mississippi, 2006)
"What happened to the Vietnam protesters and civil rights activists? Where did their idealism lead them? And what do they feel they have contributed to the nation's political debate? Answers to these and many other questions can be found in the first-hand narratives, history, and photographs of Where Have All the Flower Children Gone? Gurvis examines little-known aspects of the 1960s such as an uprising at Colorado State and coffeehouses that helped soldiers form opinions about Vietnam." "Where Have All the Flower Children Gone? puts a contemporary face on the Age of Aquarius. Gurvis interviews such officials as Senator Chuck Hagel (R-Nebraska) and such high-profile former radicals as Bernadine Dohrn. The book also provides one of the last interviews with the late Ossie Davis. The major and minor players of Kent State and Jackson State, where students and others perished at the hands of soldiers, weigh in as well as do the generations preceding and succeeding the Baby Boomers."--Jacket.